CONTROLLED-RELEASE OF PIROXICAM FROM CHITOSAN BEADS - (:unkn) unknown (ELSEVIER SCIENCE BV, 1995)
Piroxicam-loaded chitosan gel beads were prepared by dropping drug-containing solution of chitosan into tripolyphosphate solutions. The droplets instantaneously formed gelled spheres by ionotropic gelation. The mean diameter of beads was about 0.9 mm and drug-loading capacity was 90%. The drug was successfully encapsulated at pH 5. The release of piroxicam from chitosan beads was strongly affected by the method of drying and chitosan concentration. However, the release was not particularly affected by the other factors such as the drug and tripolyphosphate concentrations, volume of the external phase and the type of chitosan. The results were examined kinetically. When the release data were fitted to the simple power law equation, the mode of drug release was of the non-Fickian and super case II types.
Keywords: CONTROLLED RELEASE; PIROXICAM; CHITOSAN BEAD; COMPLEX